Electronic structure and the properties of solids : the physics of the chemical bond - Harrison, Walter A. (Walter Ashley), 1930- (Dover Publications, 1989)
This innovative text offers basic understanding of the electronic structure of covalent and ionic solids, simple metals, transition metals and their compounds. It also explains how to calculate dielectric, conducting and bonding properties for each. With a useful "Solid State Table of the Elements."